Dampak Penggunaan Gadget pada Kesehatan Mental dan Motivasi Belajar Siswa di Sekolah - Ilham Kamaruddin; Ferdinand Salomo Leuwol; Rahman Pranovri Putra; Mia Aina; Dina Mayadiana Suwarma; Rosa Zulfikhar (Journal on Education, 2023)
This study aims to analyze the impact of gadget usage on the mental health and learning motivation of students in schools through a literature review. The method used in this study is literature analysis from sources relevant to the research topic. The analysis results indicate that gadget usage has an impact on students' mental health, such as anxiety, stress, and gadget addiction. Gadget usage also has an impact on students' learning motivation, such as a decrease in interest in learning and concentration. To address these negative impacts, a holistic approach is needed, such as limiting gadget usage time, using creative and innovative learning methods, and providing social support from family and friends.